The Cambridge history of early modern English literature - Loewenstein, David (2002)
Introduction /David Loewenstein, Janel Mueller –1. Modes and means of literary production, circulation and reception: –Literacy, society and education /Kenneth Charlton, Margaret Spufford –Manuscript transmission and circulation /Harold Love, Arthur F. Marotti –Print, literary culture and the book trade /David Scott Kastan –Literery patronage /Graham Parry –Languages of early modern literature in Britain /Paula Blank –Habits of reading and early modern literary culture /Steven N. Zwicker –2. The Tudor era from the reformation to Elizabeth I: –Literature and national identity /David Loades –Literature and the court /William A. Sessions –Literature and the church /Janel Mueller –3. The era of Elizabeth and James VI: –Literature and national identity /Claire McEachern –Literature and the court /Catherine Bates –Literature and the church /Patrick Collison –Literature and London /Lawrence Manley –Literature and the theatre /David Bevington –4. The earlier Stuart era: –Literature and national identity /Johann P. Sommerville –Literature and the court /Leah S. Marcus –Literature and the church /Debora Shuger –Literature and London /Thomas N. Corns –Literature and the theatre to 1660 /Martin Butler –Literature and the household /Barbara K. Lewalski –5. The civil war and commonwealth era: –Literature and national identity /Derek Hirst –Literature and religion /David Loewenstein, John Morrill –Literature and London /Nigel Smith –Literature and the household /Helen Wilcox –Alternative sites for literature /Joshua Scodel –From revolution to restoration in English literary culture /James Grantham Turner.